Association of somatic problems with mental health among sickle cell anaemic adolescents of Chhattisgarh, India - Ogre, Shyama Charan; Shrivastava, Priyamvada; Chakravarty, Moyna (International Journal Of Community Medicine And Public Health, 2018)
Background: The sickle cell disease is characterized by various somatic problems and medical complications with psychological problems. Sickle cell patient faces physical, economical and psychological burden. There is paucity of evidences in understanding the bio-psychological aspects of sickle cell anaemic patients especially in India. Therefore, an attempt has been made to know the somatic problems in adolescents and its effects in mental health of the adolescents suffering from sickle cell anaemia. The main aim was to find out association of somatic problems with mental health among adolescents suffering from sickle cell anaemia and occurrence of somatic problems among homozygous/heterozygous sickle cell adolescents Methods: The total sample of the study consists of 309 sickle cell anaemic adolescents of age range 11-19 years. The information was collected for present research from various hospitals and health clinics of Chhattisgarh state during January, 2013 to July, 2015. An interview-schedule was prepared to know the various somatic problems and other related information. Mental Health Battery (Hindi version) was used to assess the mental health among sickle cell anaemic adolescents developed by Singh and Gupta, 1983. Results: The study revealed that 23.3 percent of the cases were homozygous whereas 76.7 percent cases were heterozygous. The overall contribution of mental health dimension are 28.0% (R2=.280; F (3,304) =31.250; p<0.01) in which two predictors of mental health namely Emotional Stability and Overall Adjustment contributed significantly. Total 84.1 percent patients were reported somatic problems and somatic problems of sickle cell patients are significantly and negatively related to all dimensions of mental health. Conclusions: For reducing the somatic problems, mental health of the adolescents will have to be increased.